Understanding barriers and facilitators to doxycycline post-exposure prophylaxis adherence among young women in western kenya: a qualitative study - Benn Kwach; Zachary Kwena; Lauren R. Violette; Bernard Rono; Josephine B. Odoyo; Kevin Oware; Elizabeth A. Bukusi; Jared M. Baeten; Lucy Mkandawire-Valhmu; Jenell Stewart; dPEP Kenya Study Team (BMC Infectious Diseases)
Abstract Sexually transmitted infection (STI) rates are high globally, particularly in regions like sub-Saharan Africa, where there is also a disproportionate burden of HIV. Doxycycline post-exposure prophylaxis (doxyPEP) is a novel strategy intended to prevent bacterial STIs following potential exposure. The dPEP Kenya Study, the first trial of doxyPEP for STI prevention among cisgender women, found that doxyPEP did not reduce STIs in the setting of low use of doxyPEP by objective drug concentrations. To assess barriers and facilitators to doxyPEP adherence, we explored participants' experiences during the dPEP Kenya Study. We conducted serial in-depth interviews (n = 40) and 4 focus group discussions (n = 29) of participants randomized to take doxyPEP. Transcripts were analyzed using an inductive content analysis approach. Side effects, such as nausea from taking doxyPEP on an empty stomach, dosage interpretation challenges, pill burden, and concerns about stigma and partner reactions hindered adherence. Support from partners, family, and peers, familiarity with doxycycline, and the use of discreet pill carriers facilitated doxyPEP use. Decreasing dosage frequency, promoting the use of discreet pill carriers, and addressing stigma through community-driven communication strategies may improve future doxyPEP uptake and adherence. Clinical trial number. This trial was registered in the ClinicalTrials.gov under registration number, NCT04050540 on 06th August 2019.